因式分解(1)1-36b^2(2)12x^2-3y^2(3)0.49p^2-144 (4)(2x+y)^2-(x+2y)^2

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/03 22:56:15
因式分解(1)1-36b^2(2)12x^2-3y^2(3)0.49p^2-144 (4)(2x+y)^2-(x+2y)^2
xŐOK@ƿ3_$!u۞ [NbeWe].>Nx~ɳ*hQbQ@Z$dLЬ,jY XXukS`&뿽BO#HE5o"+ޢGRUۋz 'I |dhN)S@v~0}@J"AfMHх\MOã@2 ~XRd) ^rmJdDT`$x l]A`mX;>6 S3c+mgGs->s~qz.GO⮘y6揋b6*'ok>}l

因式分解(1)1-36b^2(2)12x^2-3y^2(3)0.49p^2-144 (4)(2x+y)^2-(x+2y)^2
因式分解(1)1-36b^2(2)12x^2-3y^2(3)0.49p^2-144 (4)(2x+y)^2-(x+2y)^2

因式分解(1)1-36b^2(2)12x^2-3y^2(3)0.49p^2-144 (4)(2x+y)^2-(x+2y)^2
(1)1-36b^2=(1+6b)(1-6b)
(2)12x^2-3y^2
=3(4x²-y²)
=3(2x+y)(2x-y)
(3)0.49p^2-144=(0.7p+12)(0.7p-12)
(4)(2x+y)^2-(x+2y)^2
=[(2x+y)+(x+2y)][(2x+y)-(x+2y)]
=(3x+3y)(x-y)
=3(x+y)(x-y)

(1)1-36b^2
=1²-(6b)²
=(1+6b)(1-6b)

(2)12x^2-3y^2
=3(4x²-y²)
=3(2x+y)(2x-y)

(3)0.49p^2-144
=(0.7p)²-12²
=(0.7p+12)(0.7p-12)

(4)(2x+y)^2-(x+2y)^2
=[(2x+y)+(x+2y)][(2x+y)-(x+2y)]
=(3x+3y)(x-y)
=3(x+y)(x-y)

(1-6b)(1+6b),(0.7p-12)(0.7p+12),3(2x+y)(2x-y),3(x+y)(x-y),7答案16(m^2+1)+20m,8答案175.84平方厘米…作业刚好一样